Acute Effects of Heel-to-Toe Drop and Speed on Running Biomechanics and Strike Pattern in Male Recreational Runners: Application of Statistical Nonparametric Mapping in Lower Limb Biomechanics - Yu, Peimin; He, Yuhuan; Gu, Yaodong; Liu, Yuwei; Xuan, Rongrong; Fernandez, Justin (Frontiers in Bioengineering and Biotechnology, 2022)
With the increased popularity of running, many studies have been conducted into footwears that are highly related to running performance and running-related injuries. Previous studies investigated different shoe types and running shoes with different heel-to-toe drops (HTDs). However, no research was found in investigating shoes with negative values with HTD. Therefore, the aim of this study was to determine the acute effect of HTD and running speed on lower limb biomechanics and strike pattern in recreational runners. Thirteen male recreational runners wearing shoes with two different HTDs (−8 and 8 mm) performed running at three different speeds (preferred speed [PS], 90% of PS, 110% of PS). Lower extremity kinematics and ground reaction forces were synchronously captured via Vicon motion analysis system and AMTI force platform. Strike index (SI), vertical average loading rate (VALR), vertical instantaneous loading rate (VILR), excursion, eversion duration, joint angles, and range of motion (ROM) of metatarsophalangeal (MTP), ankle, knee, and hip joints were calculated. Joint angles during the entire stance phase were analyzed applying the statistical nonparametric mapping (SnPM) method. SI and VILR in shoes with −8 mm HTD significantly increased by 18.99% and 31.836 BW/s compared to those with 8 mm HTD (SI: p = 0.002; VILR: p < 0.001). Significant alterations of ROM occurred in the MTP, ankle, and knee joints (p < 0.05), and HTD factor primarily accounted for these changes. Joint angles (MTP, knee, and hip) during the entire stance phase altered due to HTD and speed factors. Running speed primarily influenced the kinematics parameters of knee and hip joints, increasing knee angles in the frontal plane and hip angle in the horizontal plane at PS (p > 0.05). Compared to shoes with 8 mm HTD, shoes with −8 mm HTD may be useful to storage and return energy because of the increased ROM of MTP in the sagittal plane. Besides, forefoot strike gait retraining was recommended before transition from normal running shoes to running shoes with −8 mm HTD.